How Closely Related Are Parent and Child Reports of Child Alexithymia? - Lampi, Andrew J.; Jaswal, Vikram K.; Evans, Tanya M. (Frontiers in Psychology, 2021)
Alexithymia is a subclinical trait involving difficulty describing and identifying emotions. It is common in a number of psychiatric conditions. Alexithymia in children is sometimes measured by parent-report and sometimes by child self-report, but it is not yet known how closely related the two measures are. This is an important question both theoretically and practically, in terms of research design and clinical practice. We conducted a preliminary study to investigate this question in a sample of 6- to 11-year-old neurotypical children and their parents (N = 29 dyads). Parent and child reports were not correlated, and 93% of parents underestimated their child’s level of alexithymia relative to the child’s self-report. Based on these results, we hypothesize that when asked to report on the child’s alexithymia, children and parents may not be reporting on the same phenomenon, and thus these two measures may not be interchangeable. These provocative findings, however, must be considered preliminary: Our analyses were sufficiently powered to detect a strong relation between the two types of report had one existed, but our analyses were not sufficiently powered to distinguish between a small relation and no relation at all.